The Pattern of Pediatric Parasitic Skin Diseases in a Secondary Hospital in East Java: A Retrospective Study - Prakoeswa, Flora Ramona Sigit; Pramuningtyas, Ratih; Dimawan, Rully Setia Agus (Faculty of Medicine, Universitas Airlangga, 2023)
Background: Epidermal parasitic skin diseases (EPSDs) are a group of neglected infectious diseases caused by parasites that infect the upper layer of the skin. A parasitic infection of the skin is caused by small insects or worms that burrow into the skin to live there or lay their eggs. EPSDs are a public health issue and can occur in children of all ages. Purpose: This study aims to describe the pattern and incidences of parasitic skin infections in children. Methods: This is a cross-sectional study utilizing medical records from the Dermatology and Venereology Clinic of Dr. Harjono Ponorogo General Public Hospital from 2016 to 2020. Result: Our study showed that, of the 1426 children brought to our clinic, parasitic infection was the second most common skin disease found in children with a prevalence of 27.1%. Parasitic infection in children was dominated by males with a proportion of 69.7%, and occurred mostly in the â‰¥13-year-old age group. Among all ages, scabies is the most frequent parasitic infection found, followed by cutaneous larva migrant (CLM) and pediculosis. Conclusion: The prevalence of EPSDs is increasing with age and is more common in males. This high prevalence is probably due to increased intensity of contact with other people, decreased parental care, and low socio-economic status.